BUILDING POSITIVE RELATIONSHIPS: THE ROLE OF EMPATHY AND COMPASSION IN PERSONAL GROWTH - Yang, Liu; Mei, Chen; Tan, Ethan (Research Psychologie, Orientation et Conseil, 2026)
In today’s increasingly interconnected and diverse world, the ability to build positive relationships is essential for both personal and professional success. Empathy and compassion are two core interpersonal skills that contribute to stronger connections and greater well-being. These qualities not only enhance relationships but also promote personal growth by fostering understanding, emotional resilience, and a sense of shared humanity. However, the specific role of empathy and compassion in personal development remains underexplored. This study aims to examine the role of empathy and compassion in building positive relationships and promoting personal growth. The research investigates how these two traits influence emotional intelligence, self-awareness, and interpersonal communication in diverse contexts. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 250 participants across various age groups and professions. The findings revealed that higher levels of empathy and compassion were associated with improved interpersonal relationships and greater personal growth. Participants who reported stronger empathy and compassion exhibited better emotional regulation, higher self-awareness, and more positive social interactions. This study concludes that empathy and compassion are integral to building positive relationships and fostering personal growth.